COMMODITY ASPECTS OF THE INSURANCE STOCK OF GOODS IN THE STORE: FEATURES OF CALCULATION AND FORMATION - DRAZHNYTSIA, SERHII; DRAZHNYTSIA, OLEH (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The main prerequisite for the stability and continuity of trade is the formation of optimal inventories of trade entities and their effective management. It depends on how much the range of goods of the store will meet the demands of consumers, and hence the social and economic efficiency of the store. However, excessive, irrational accumulation of inventories by the business entity leads to "freezing" of working capital and reduce their turnover, which in turn reduces the efficiency of their use and profitability of the store as a whole. In addition, inventories and their volume in the trading company are influenced by a number of factors, including the characteristics of the commodity characteristics of the goods themselves. Thus, given the peculiarities of economic activity of trade entities at the present stage of national and world economy, including those caused by the global pandemic Kovid-19 and the post-quarantine period, it is extremely important to ensure the smooth functioning of trade entities through the formation and effective management insurance stock. Thus, the competent formation and management of insurance stocks of goods in the store, including taking into account the commodity characteristics of the goods themselves, provides retailers with stable and uninterrupted trade. and unavoidable costs that do not always pay off. Therefore, we offer the following steps to save on the insurance reserve: increase or decrease the planning horizon or supply frequency, increase supplier discipline, aggregate data on several product items, increase the number of available statistics over time through sales statistics, aggregate sales history by several warehouses. These methods will help reduce the amount of excess inventory in the warehouse, without compromising the quality of service, sales and peace of mind of the entrepreneur.